PENGARUH PENAMBAHAN EKSTRAK KULIT PISANG (Musa sp.) SEBAGAI SUMBER ANTIOKSIDAN PADA PRODUKSI TAHU PUTIH - Anisa, Hida Arliani Nur; Sari, Myra Wardati; Riani, Yopi (Jurnal Teknologi Pangan dan Gizi, 2020)
High antioxidant content of banana peel can be utilized as a source of antioxidant for other foodstuffs so it will be more economically valuable. One of foodstuffs that can be added by banana peel extract is tofu. However, adding banana peel extract as a source of antioxidant to the production of tofu need to be studied further related to the shelf life of tofu base on total microbes. This study aims to find out the effect of adding banana peel extract as a source of antioxidant to the production of white tofu. Stages of research: 1) The making of banana peel extract, 2) Antioxidant test of banana peel extract, 3) Phytochemical test of extract, 4) Production of tofu with the combination of banana peel extract with variations in concentration namely 5%, 10%, and 15%, 5) The extraction of fortification tofu, 6) Test of tofu antioxidant activity, and 7) Test with TPC test. The result ahow that banana peel extract contains alkaloid, tannins, flavonoid, steroids and triterpenoid. Banana peel extract shows the antioxidant activity as much as 58,02%. The addition of banana peel extract in the production of tofu is the most optimum at the concentration of 15% with a shelf life of 1 day at room temperature that show antioxidant activity as much as 51,87%. The best TPC value on tofu with banana peel extract is produced at concentration of 15% with a shelf life of 1 day at room temperature.